2023
DOI: 10.3389/fpls.2023.1101143
|View full text |Cite
|
Sign up to set email alerts
|

Automatic counting of rapeseed inflorescences using deep learning method and UAV RGB imagery

Abstract: Flowering is a crucial developing stage for rapeseed (Brassica napus L.) plants. Flowers develop on the main and branch inflorescences of rapeseed plants and then grow into siliques. The seed yield of rapeseed heavily depends on the total flower numbers per area throughout the whole flowering period. The number of rapeseed inflorescences can reflect the richness of rapeseed flowers and provide useful information for yield prediction. To count rapeseed inflorescences automatically, we transferred the counting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…The authors also reported difficulties occurring in training and detection due to multiple inflorescences overlapping as occlusions. This type of under-detection caused by inflorescence overlap was also reported by Li et al, (2023) [49] in the effort to count B. napus inflorescences using UAV-acquired imagery to train CenterNet CNN models.…”
Section: Statistical Precisionsupporting
confidence: 65%
“…The authors also reported difficulties occurring in training and detection due to multiple inflorescences overlapping as occlusions. This type of under-detection caused by inflorescence overlap was also reported by Li et al, (2023) [49] in the effort to count B. napus inflorescences using UAV-acquired imagery to train CenterNet CNN models.…”
Section: Statistical Precisionsupporting
confidence: 65%
“…Additionally, Chen and Liao [21] provided fast region-based convolutional neural network (Fast R-CNN) architecture to detect and classify palm trees. Li et al [22] developed a low-cost approach for counting rapeseed inflorescences using YOLOv5 with the convolutional block attention module based on UAV RGB imagery. A similar study was also conducted in the counting of rice seedlings and achieved a promised recognition accuracy [23].…”
Section: Introductionmentioning
confidence: 99%